The role of epidermal growth factor receptor (EGFR) in the efficacy of neoadjuvant chemotherapy in triple-negative breast cancer patients - N. N. Babyshkina; T. A. Dronova; E. A. Zambalova; M. V. Zavyalova; E. M. Slonimskaya; N. V. Cherdyntseva (Бюллетень сибирской медицины)
Background. Identification of predictive molecular markers of triple-negative breast cancer (TNBC) will enable the evaluation of the efficacy of neoadjuvant chemotherapy (NACT) and define optimum approaches for the prognosis of the disease course in TNBC patients.The aim of the study was to examine the correlation between the expression of the epidermal growth factor receptor (EGFR), its gene’s polymorphic variants and the neoadjuvant chemotherapy (NACT) efficacy in triple-negative breast cancer (TNBC) patients.Materials and methods. The study included 70 patients with triple-negative breast cancer, who had received 2-4 cycles of FAC and CAX regimens. The efficacy of the neoadjuvant chemotherapy was assessed according to the RECIST scale. The EGFR expression level in tumors before and after the NACT was evaluated with the help of immunohistochemistry. Genotypes for EGFR (rs2227983 and rs1468727) were detected by a real-time PCR.Results. It was found that NCT significantly decreases the EGFR expression level in the tumor (p = 0.000). The research associates the objective clinical response as well as the pathological complete response with the low EGFR expression level (p = 0.007 and p = 0.000 respectively). Patients carrying the EGFRCC mutant genotype of rs1468727 did not achieve a pathological complete response (p = 0.042). In addition, patients with EGFRCC mutant genotype are more likely to have tumors with a high EGFR expression compared to EGFRTT wild-type genotype patients (p = 0.047).Conclusion. The EGFR expression level in tumor tissue and the polymorphic variants of its gene in the rs1468727 locus can be considered as potential molecular markers with predictive significance in relation to the NACT efficacy in triple-negative breast cancer patients.